2016
DOI: 10.18869/acadpub.jafm.68.224.23991
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady/Steady Hydromagnetic Flow of Reactive Viscous Fluid in a Vertical Channel with Thermal Diffusion and Temperature Dependent Properties

Abstract: The problem of unsteady as well as steady hydromagnetic natural convection and mass transfer flow of viscous reactive, incompressible and electrically conducting fluid between two vertical walls in the presence of uniform magnetic field applied normal to the flow region is studied. Thermal diffusion, temperature dependent variable viscosity and thermal conductivity are assumed to exist within the channel. The governing partial differential equations are solved numerically using implicit finite difference schem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…It has various application such as in petroleum industry, purification of crude oil, pumps accelerators and power generators (1). Researchers have took a great interest investigated problem regarding free convection flow between two parallel plates (2,3). Oscillatory flow between parallel plates have received some attention between the researchers.…”
Section: ________________________________________________________________ R E S E a R C H O B J E C T I V E Smentioning
confidence: 99%
“…It has various application such as in petroleum industry, purification of crude oil, pumps accelerators and power generators (1). Researchers have took a great interest investigated problem regarding free convection flow between two parallel plates (2,3). Oscillatory flow between parallel plates have received some attention between the researchers.…”
Section: ________________________________________________________________ R E S E a R C H O B J E C T I V E Smentioning
confidence: 99%
“…Literature reviews of References 14–18 revealed that many scholars are concerned about mechanisms like the fluid flow between two parallel plates. Still, none of them considers oscillations between two parallel plates.…”
Section: Introductionmentioning
confidence: 99%